Does the Government really care about the Citizens? Exploring the Impact of Fuel Subsidy Removal on Crime Rate in Benin City, Edo State, Nigeria - Omigie, Sunday Oseye; Uwagbale, Francis Raymond (NIU Journal of Humanities; Vol. 10 Núm. 1 (2025): NIU Journal of Humanities, Vol. 10 No. 1, March 2025, 2025)
This intriguing study delved into the government's decision to eliminate subsidies on petroleum prices and how this move has influenced crime rates in the vibrant city of Benin, Edo State. The research aimed to uncover the connection between the withdrawal of fuel subsidies and the alarming rise in criminal activities, as well as to assess the repercussions of this policy change on social unrest across different socioeconomic groups in the city. The study focused on residents aged 18 and older, gathering insights from a sample of 156 individuals selected through a random sampling method. Employing a mix of descriptive statistics—like frequencies, percentages, and tables—and inferential statistics, including p-values, t-values, and F-statistics, the analysis revealed a striking correlation: the removal of fuel subsidies is significantly linked to the uptick in crime rates in Benin City. Furthermore, it highlighted that this policy shift has notably impacted criminal behavior and social unrest among various socioeconomic demographics within the community. Finally, the study recommends that removing subsidies must be done gradually and strategically. Initiatives that are specifically tailored to alleviate socio-economic inequality are crucial and that thorough approach that incorporates economic diversification, crime prevention, and continuous monitoring is advised Keywords: Fuel Subsidy Removal, Crime Rate, Criminal Activity, Social Unrest.